2023
DOI: 10.1002/brb3.3008
|View full text |Cite
|
Sign up to set email alerts
|

Conflict in a word‐based approach‐avoidance task is stronger with positive words

Abstract: Background Valence and motivational direction are linked. We approach good things and avoid bad things, and experience overriding these links as conflicting. Positive valence is more consistently linked with approach than negative valence is linked with avoidance. Therefore, avoiding positive stimuli should produce greater behavioral and neural signs of conflict than approaching negative stimuli. Methods In the present event‐related potential study, we tested this assumption by contrasting positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…Interestingly, when examining the congruency effect for positive and negative feedback separately, we found that the congruence effect for positive feedback is greater than that of negative social feedback. This pronounced congruence effect in response to positive feedback is consistent with previous findings reporting stronger stimulus-response compatibility effects with positive stimuli (e.g., positive words, happy faces, appetitive food, and butterflies) than with negative stimuli (negative words, angry faces, spoiled food, and spiders) in an approachavoidance task (Klackl et al, 2023;Stins et al, 2011). Positive stimuli typically elicit approach behaviors, whereas negative stimuli can trigger a variety of defensive actions including avoidance (e.g., freezing, rejecting) and approach behavior (e.g., anger) (Carver & Harmon-Jones, 2009;Lang et al, 1997).…”
Section: Effect Of Self-relevant Social Feedback On Approach-avoidanc...supporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, when examining the congruency effect for positive and negative feedback separately, we found that the congruence effect for positive feedback is greater than that of negative social feedback. This pronounced congruence effect in response to positive feedback is consistent with previous findings reporting stronger stimulus-response compatibility effects with positive stimuli (e.g., positive words, happy faces, appetitive food, and butterflies) than with negative stimuli (negative words, angry faces, spoiled food, and spiders) in an approachavoidance task (Klackl et al, 2023;Stins et al, 2011). Positive stimuli typically elicit approach behaviors, whereas negative stimuli can trigger a variety of defensive actions including avoidance (e.g., freezing, rejecting) and approach behavior (e.g., anger) (Carver & Harmon-Jones, 2009;Lang et al, 1997).…”
Section: Effect Of Self-relevant Social Feedback On Approach-avoidanc...supporting
confidence: 91%
“…A seminal work by Solarz (1960) using implicit AAT first demonstrated that the valence of words impact approach/avoidance behavior. This finding has been replicated across countless studies using stimuli such as attitude objects (Chen & Bargh, 1999), adjectives (Seibt et al, 2008), and abstract nouns (Citron et al, 2016;Klackl et al, 2023).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation